PENERAPAN ASESMEN UNJUK KERJA MATERI MENULIS TEKS EKSPLANASI KELAS XI SMA AL FALAH JAMBI - Nur Hidayat; Andiopenta Purba; Akhyaruddin Akhyaruddin (Universitas Batanghari, 2022)
This study aims to examine the application of the assessment of the performance of writing explanatory texts for class XI SMA Al Falah Jambi by looking at how the teacher designs, implements, and evaluates performance results in learning to write explanatory texts. This study uses a descriptive-qualitative approach. The subject of this research is the Indonesian class XI teacher. Data collection techniques were carried out by observation, interviews and documentation of the subject and object of research. The results showed that the teacher implemented a performance assessment guided by the lesson plan, the implementation of the performance assessment had been carried out well in accordance with the assessment development steps for the type of product and portfolio assessment, but there were obstacles in implementing the performance assessment experienced from internal and external factors. As a suggestion should use the appropriate assessment to measure the skills of learners effectively. So that more in-depth research needs to be done.